Social assimilation and immigrants’ labour market outcomes - Piracha, Matloob; Tani, Massimiliano; Cheng, Zhiming; Wang, Ben Zhe (My University, 2022)
We analyse how immigrants’ level of social assimilation is related to their labour market outcomes. More precisely, we estimate the association between assimilation and employment, wages, underemployment, three measures of job satisfaction, overeducation and wages. Using Australian longitudinal data, we find that assimilation is strongly associated with employment and wages as well as a number of job satisfaction measures. We then split our data and repeat the analysis for before and after the financial crisis of 2008–2009. We find important differences in the way assimilation is associated with different measures of labour market outcomes under different economic conditions. Finally, we explore mechanisms that may underlie the results.
Journal of Population Economics
Keywords: Income, wealth and finances; Labour market; Migration and settlement